2019
DOI: 10.22606/fmr.2019.31003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patients’ Perception of Healthcare Professionals’ Ethics in Bangladesh

Abstract: Employees in organizations face a myriad of moral issues in their everyday decisionmaking. It is of great significance when the decisions entail a professional conduct where the individuals have fiduciary relationship with one or more stakeholders-as in the case of doctors and patients. In the healthcare sector of Bangladesh, a number of malpractices and unethical behaviours have been highlighted in the media and by the insiders to the industry. Hence, the aim of this exploratory research was to see the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The taxonomy of above ideologies has been summarized in Figure 1. Another study conducted in Bangladesh by Ahmed (2019) observed that the pharmaceutical and medical equipment companies pay huge kickbacks to health-care professionals to increase the sales of their companies. However, these marketing costs are passed on to the patients, as an increase in the price of the drugs.…”
Section: Prescription Behavior Of Physiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomy of above ideologies has been summarized in Figure 1. Another study conducted in Bangladesh by Ahmed (2019) observed that the pharmaceutical and medical equipment companies pay huge kickbacks to health-care professionals to increase the sales of their companies. However, these marketing costs are passed on to the patients, as an increase in the price of the drugs.…”
Section: Prescription Behavior Of Physiciansmentioning
confidence: 99%
“…Evolving technologies and improved civilization have changed companies’ ways of work over time, as most of them use strategies that support them in improving sales in a competitive environment (Ahmed, 2019). Further, rapid population growth and economic developments have led pharmaceutical companies to improve health-care services with greater availability of pharmaceutical products (Ahmed et al , 2014).…”
Section: Introductionmentioning
confidence: 99%